(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2025)
Linear differential equations are fundamental tools in the analysis and modeling of dynamical systems that are used in many physical and engineering phenomena. This paper examines the structure, properties, and applications of these linear equations in the analysis of mass-spring systems, RLC circuits, and heat transfer processes. By presenting mathematical models and analyzing the time responses of these systems, it is shown how linear equations can model complex behaviors in a simple, predictable, and robust manner. The results of this research show that linear differential equations, despite their simplicity, are effective tools for the analysis of physical systems, and are used to more accurately model more complex systems over time.